(untitled) (Semiárida, 2024)
. In the semi-arid Pampas Region, the spatial heterogeneity observed through patches characterized by lower production and persistence of perennial pastures is increasingly frequent from the second year onwards. The objective was to relate the growth and development of a pure lucerne pasture and another associated with the physical-hydric characteristics of the soil in patch and normal environments. In addition, it is planned to evaluate the effect of the environment on the phosphorus and organic matter content of the soil. Lucerne and lucerne + fescue were planted on a Petrocalcium Paleustol in 2020. In 2023, saturated hydraulic conductivity (CH), bulk density (DA) and total porosity (PT). Organic matter (MO) and extractable phosphorus content (P) were evaluated on the patch and normal area. Biomass production was 41 and 46 % lower under patch compared to the normal situation in A and A+F, respectively in both pastures it was found that the CH and PT measured 6-12 y 12-18 cm was higher in the normal sector, with respect to the patch. The P content in the patchy sector was higher by 59 and 20 % for 0-10 and 10-20 cm depth, respectively, with respect to the normal sector. Regarding the MOT content, the initial value (year 2020) was similar to that measured in the year 2023 in the spot sector for 0-10 cm depth, however in the normal sector the MO content increased by 16 %. In lucerne + fescue, the MO content in the patchy sector in 2023 was also similar to the initial content, but in the normal sector, the increase was 11 %. For the depth of 10-20 cm, the soil with lucerne presented similar MO contents between 2020 and both sectors in 2023. On the other hand, for lucerne + fescue in the patch sector the MO content was significantly lower with respect to the beginning and the sector normal (2023). The soil indicators evaluated in the areas under patch in lucerne and lucerne + fescue presented lower values of CH, PT and MO with respect to normal soil areas, on the other hand, the P content was higher under patch with respect to normal areas, probably due to the lesser extraction of the nutrient over the years.